The Family of Francis Marion Shaw Newsletter Volume 18 Number 1 - Shaw, Bryan Lee (My University, 2010)
This newsletter profiles Leonard Cleo Shaw, a grandson of Francis Marion and Rachel Moore Allen Shaw, whose life was significantly shaped by his heritage but defined by a long and successful career in the lumber industry. Born in Willacoochee, Georgia, into a family primarily involved in the naval stores business, Cleo's early life included time on a farm before his family moved to Ray City. At age 16, he began working in the lumber industry, eventually securing a life-changing employment opportunity in 1925 with Weaver-Loughridge Lumber Company in Perry, Florida, which later became Pinellas Lumber Company. He spent 46 years with this company, rising to the position of Comptroller before his retirement in 1971, also serving as auditor, secretary, and treasurer for Derby Lane, an affiliate. Leonard, known as "L.C.", was a self-educated man with a keen understanding of finance, a dedicated family man who, with his wife Beulah Cason, raised four children in St. Petersburg, Florida, and was known for his honesty and community involvement. He passed away in 1987, having dedicated his life to "one company, one family, and one principle, honesty".
This item contains 1 PDF with 4 pages in addition to 4 JP2 files
Keywords: Berrien County (Ga.); Berrien County Historical Foundation (Nashville; Ga.); Nashville (Ga.); Newsletters; Periodicals; Berrien County (Ga.)--History--Sources; Electronic records; Grady County (Ga.)--History; Historic preservation--Georgia--Berrien County; Georgia--Genealogy